2019
DOI: 10.1186/s12879-019-3936-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of Toxoplasma gondii among pregnant women in Adwa district, northern Ethiopia

Abstract: Background Toxoplasma gondii infection is a great health concern to pregnant women and the developing fetus. The aim of this study was to determine the seroprevalence of T. gondii and its associated factors in Adwa district. Methods A facility based cross-sectional study was conducted from January to June 2018 in Adwa district. Structured, a pre-tested questionnaire was used to collect the demographic and risk factor related dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 37 publications
1
22
0
2
Order By: Relevance
“…It is reported that the sexual multiplication of T. gondii takes place in cats and hence cats excrete the unsporulated oocysts with faeces in the environments [4,57]. Living or contact with cat were found to be the independent predictors of T. gondii infection (p<0.05) [11,21,23,27,29,34]. Whereas only one study did not find any association of living or contact with domestic animals such as cat and being infected with T. gondii among pregnant women [45].…”
Section: Risk Factorsmentioning
confidence: 97%
See 3 more Smart Citations
“…It is reported that the sexual multiplication of T. gondii takes place in cats and hence cats excrete the unsporulated oocysts with faeces in the environments [4,57]. Living or contact with cat were found to be the independent predictors of T. gondii infection (p<0.05) [11,21,23,27,29,34]. Whereas only one study did not find any association of living or contact with domestic animals such as cat and being infected with T. gondii among pregnant women [45].…”
Section: Risk Factorsmentioning
confidence: 97%
“…In this review, other predictors of T. gondii seropositivity were the consumption of raw vegetables or fruits. A significant association was observed between T. gondii seropositivity and eating raw or unwashed vegetables or fruits [20,21,28,30,35,37,44].…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the three principal routes of toxoplasmosis transmission, consumption of unwashed vegetables and fruits contaminated with cat feces is an important one that sometimes may lead to food-borne outbreaks [57]. The significant association of T. gondii infections with the consumption of contaminated raw vegetables is also observed in previous studies [58][59][60]. The detection of Toxoplasma gondii in contaminated vegetables and fruits is usually performed by PCR amplification [23,[61][62][63].…”
Section: Entamoeba Contaminationmentioning
confidence: 99%